Magical progeny, modern technology : a Hindu bioethics of assisted reproductive technology - Bhattacharyya, Swasti, 1963- (State University of New York Press, 2006)
"Magical Progeny, Modern Technology examines Hindu perspectives on assisted reproductive technology through an exploration of birth narratives in the great Indian epic the Mahabharata. Author Swasti Bhattacharyya weaves together elements from South Asian studies, religion, literature, law, and bioethics, as well as experiences from her previous career as a nurse, to construct a Hindu response to the debate. Through analysis of the mythic stories in the Mahabharata, specifically the birth narratives of the five Pandava brothers and their Kaurava cousins, she draws out principles and characteristics of Hindu thought. She broadens the bioethical discussions by applying Hindu perspectives to a California court case over the parentage of a child conceived through reproductive technology and compares specific Hindu and Roman Catholic attitudes toward assisted reproductive technology. Magical Progeny, Modern Technology provides ways to explore ethical issues and highlights concerns often overlooked in contemporary discussions occurring within the United States."--Jacket.